Relationship between aggressive behavior and reading achievement among students with reading disabilities in Ibadan, Oyo state (2015)
This study investigated the relationship between aggressive behaviour and reading achievement of students with reading disabilities in lbadan, using the descriptive survey design. Two hundred and eighty-two (282) students with reading disabilities from seven secondary schools were randomly selected in four local, government areas in Ibadan. The study used an adapted version of the Learning Disabilities Screening Inventory by Learning Disabilities Association of Ontario (LDAO, r=0.63, the Reading Disabilities Screening Test (RDST, r-0.70), the Students' Test of Reading (STR, r-0.72), and the Beliefs about Aggression and Alternative (BAA, r-0.72). Pearson Product Moment Correlation (PPMC) was used to answer one research question generated, while t-test statistics was used to test the three hypotheses generated al 0.05 level of significance. The results showed that there was a signifìcant relationshipip between aggressive behaviour and reading achievement (r= -0.719, P<.05). This portrays that high aggressive behaviour would definitely lead to decreased reading achievement among students with reading disabilities, and vice versa. Also, there were signifìcant differences in aggressive behaviour and gender (F-5.049, df=280, p< 0.05); family type (F=11.004, df=280, p< 0.05); and. school type (F=9.280, df=280, p< 0.05). It was recommended that general and special educators working with students with reading disabilities should consciously implement effective strategi.es to control, manage and curb aggressive behaviours of the students so as to improve their reading and academic achievement.